Ultrastructure of the mental gland of the Red‐Backed Salamander, Plethodon cinereus (Amphibia: Plethodontidae). (18th January 2016) - Sever, David M.
Abstract: Mental glands are sexually dimorphic glands found in the skin of the submandibular region in males of many species in the salamander family Plethodontidae. These glands have been demonstrated to secrete pheromones that increase female receptivity to courtship and mating. A number of studies exist on the morphology of mental glands at the light microscopy level, but ultrastructural studies on the glands exist for only two species, Eurycea quadridigitata and Hydromantes italicus . In this study, ultrastructure of the mental gland is described from seasonal samples of the eastern North American plethodontid Plethodon cinereus . The mental glands are most hypertrophied in males examined in mating condition (i.e. sperm in their Wolffian ducts) in October and April. In these specimens, 6‐ to 8‐μm electron‐dense secretory vacuoles are found in the apical cytoplasm (October) or throughout the entire epithelial cells (April). Mental glands from June and August contain only condensing vacuoles, and the cytoplasm is otherwise packed with stacks of rough endoplasmic reticulum. The ultrastructure of the mental gland of P. cinereus agrees with earlier descriptions for E. quadridigitata and H. italicus . Two other sexually dimorphic skin glands, the caudal courtship gland and the cloacal vent gland, were previously examined from males in this sample of P. cinereus . Although all three glands show similarities in histology and histochemistry at the light microscopy level, they are dissimilar in ultrastructure. Whereas the secretory vacuoles of mental glands are uniformly electron dense, those of caudal courtship glands are smaller (1.2–1.5 μm), oblong and biphasic, and vent glands have spherical biphasic secretory vacuoles (1.8–2.1 μm). This indicates a difference in secretory product and function for the three glands and needs further investigation. Whether other plethodontids show similar variation among sexually dimorphic glands is another topic for future research.